PROJEKTOWANIE UKŁADÓW STEROWANIA BINARNEGO WSPOMAGANE AUTOMATYCZNYM WNIOSKOWANIEM GENTZENA - Tkacz, Jacek
There are presented a new idea of an application of Gentzen logic symbolic reasoning for solving some combinational problems in the digital system design in this Ph.D. Thesis. Although there are described a particular kind of logic algorithms optimization and some possibilities of increasing efficiency of the presented application for the normalizing a great number of symbolic expressions. The new CAD system is able to transform very complicated behavioral descriptions into simple expressions, which can be directly mapped into FPGA structures. On the other hand the system produces an ESPRESSO format, which makes possibility of easy cooperate with popular university systems like VIS, SIS or DEMAIN. Proposed system could also cooperate with known commercial CAD systems by making transformation from normalized digital system description into HDL languages like VHDL and Verilog.
Keywords: technika cyfrowa; sekwent; drzewo dowodu; logika matematyczna; Gentzen; wnioskowanie symboliczne